2023
DOI: 10.1177/10556656221148368
|View full text |Cite
|
Sign up to set email alerts
|

Managing Chronic otitis media with Effusion in Children with non-Syndromic Cleft Palate: Short-Term Ventilation Tubes Versus Surveillance

Abstract: Objective To compare the effectiveness of short-term ventilation tubes compared to surveillance on conductive hearing loss in children with non-syndromic orofacial clefting involving the muscular palate. Introduction Chronic otitis media with effusion is a common finding in children with cleft palate. The accepted convention is insertion of short-term ventilation tubes at the time of palate repair, but some centres are choosing conservative management. Each approach has its advantages but there is currently no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The ideal otological management for children with cleft L/P has long been a matter of conflict 20 . Ventilation tubes were commonly used in infants with cleft L/P to prevent OME 21,22 . However, Phua et al.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The ideal otological management for children with cleft L/P has long been a matter of conflict 20 . Ventilation tubes were commonly used in infants with cleft L/P to prevent OME 21,22 . However, Phua et al.…”
mentioning
confidence: 99%
“…20 Ventilation tubes were commonly used in infants with cleft L/P to prevent OME. 21,22 However, Phua et al reported that for infants with cleft palates, selective ventilation tube insertion produced superior otologic results than preventive ventilation tube insertion. 23 It is advised that symptomatic infection or significant hearing loss is considered an indication for ventilation tube insertion.…”
mentioning
confidence: 99%